English for you: a guidebook for English language learners - Mansor, Mahani; Maesin, Anis; Osman, Nazira; Zakaria, Fazmawati; Abdul Hamid, Zaidatul Akmal; Nayan, Surina; Darus, Norizul Azida; Ahmad Zakaria, Zahrullaili; Mohamad, Raihanah; Osman, Mohd Izwan; Shafie, Latisha Asmaak (Oxford Fajar Sdn Bhd, 2013)
A guidebook for English language learners suitable for tertiary ESL education. It is designed for both beginner and intermediate level learners of English. Each of the eleven units in the books exposes the learners to different aspects of current issues that will increase their knowledge of the world. Besides suggested answers, an audio CD and a CD script are also provided for the listening practices.